2020
DOI: 10.1159/000509426
|View full text |Cite
|
Sign up to set email alerts
|

Associated Anomalies in Congenital Lung Abnormalities: A 20-Year Experience

Abstract: <b><i>Introduction:</i></b> A congenital lung abnormality (CLA) is often found in conjunction with other abnormalities but screening guidelines for newborns with CLA have not yet been reported. We aimed to assess the incidence of associated anomalies in CLA patients born or followed up at our centre and the need for additional screening of newborns with a CLA. <b><i>Methods:</i></b> From a retrospective chart review of all patients born with a CLA between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…The clinical presentation in neonates consists of recurrent wheeze or chronic cough and infections around the age of 7 months on average [ 1 , 14 ]. In some cases, the coexistence of extrapulmonary anomalies, such as congenital diaphragmatic hernia, often associated with PS, as well as cardiovascular anomalies, may suggest the presence of CLMs [ 1 , 16 , 17 ]. Postnatal complications of misdiagnosed or untreated CLMs include recurrent pneumonia (both bacterial and fungal), hemoptysis and/or hemothorax, pneumothorax, air embolism, potential tumor development, and even heart failure as a result of systemic collateral shunting [ 7 , 16 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…The clinical presentation in neonates consists of recurrent wheeze or chronic cough and infections around the age of 7 months on average [ 1 , 14 ]. In some cases, the coexistence of extrapulmonary anomalies, such as congenital diaphragmatic hernia, often associated with PS, as well as cardiovascular anomalies, may suggest the presence of CLMs [ 1 , 16 , 17 ]. Postnatal complications of misdiagnosed or untreated CLMs include recurrent pneumonia (both bacterial and fungal), hemoptysis and/or hemothorax, pneumothorax, air embolism, potential tumor development, and even heart failure as a result of systemic collateral shunting [ 7 , 16 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that 6–28.6% of PS cases occurred in association with other malformations, including CPAMs, CDH, CHD, etc. [ 8 , 13 , 15 , 33 , 35 , 40 , 41 ]. In our sample, the top 3 frequently coexisting anomalies of PS counted according to system were congenital respiratory system malformations (40.28%), circulatory system malformations (33.80%), and musculoskeletal anomalies (10.65%).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal abnormalities are associated with 1.6% of fetal pulmonary malformations, especially those with pulmonary hypoplasia and bronchial cyst ( 12 , 13 ). Therefore, invasive prenatal diagnosis such as amniocentesis is recommended for fetuses with BCs to exclude potential chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%